Traditional and disease specific risk factors for cardiovascular events in anca-associated vasculitis: A multinational retrospective study - DİRESKENELİ, RAFİ HANER (My University, 2023)
Objective To investigate the occurrence of cardiovascular events (CVEs) in a large cohort of patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) across the European Union, China, Turkey, Russia, the United Kingdom, and the USA. Methods Patients with a definite diagnosis of AAV who were followed for ≥ 3 months and had sufficient documentation were included. Data on myocardial infarction (MI) and stroke were collected retrospectively from tertiary vasculitis centers. Univariate and multivariate Cox regression models were used to estimate hazard ratios (HRs) and 95% CIs. Results Over a median follow-up of 62.0 months (IQR 22.6-100.0), CVEs (mostly MIs) occurred in 245 (10.7%) of 2286 patients with AAV, with a higher frequency in China and the UK. On multivariate regression analysis, older age (55-64.9 yrs, HR 2.93, 95% CI 1.99-4.31), smoking (HR 1.98, 95% CI 1.48-2.64), Chinese origin (HR 4.24, 95% CI 3.07-5.85), and pulmonary (HR 1.50, 95% CI 1.09-2.06) and kidney (HR 3.02, 95% CI 2.08-4.37) involvement were independent variables associated with a higher occurrence of CVEs. Conclusion We showed that geographic region and both traditional and disease-specific (kidney involvement in particular) factors were independently associated with CVEs. Proper assessment and management of modifiable cardiovascular (CV) risk factors are essential for prevention of CV morbidity in patients with AAV.